Transcriptional Regulators of Claudins in Epithelial Tight Junctions - Niamat Khan; Abdul R. Asif (Mediators of Inflammation)
Human gastrointestinal tract is covered by a monolayer of specialized epithelial cells that constitute a protective barrier surface to external toxic and infectious agents along with metabolic and digestive functions. Intercellular junctions, among epithelial cells, such as desmosomes, adherens, gap, and tight junctions (TJs), not only provide mechanical integrity but also limit movement of molecules across the monolayer. TJ is a complex structure composed of approximately 35 different proteins that interact with each other at the apical side of two adjacent epithelial cells. Claudin family proteins are important members of TJ with so far 24 known isoforms in different species. Claudins are structural proteins of TJ that help to control the paracellular movement by forming fence and barrier across the epithelial monolayer. Altered function of claudins is implicated in different form of cancers, inflammatory bowel diseases (IBDs), and leaky diarrhea. Based on their significant role in the molecular architecture of TJ, diversity, and disease association, further understanding about claudin family proteins and their genetic/epigenetic regulators is indispensable.